Bricherismo in Peruvian touristic areas: the configuration of gender in asymmetrical and intercultural encounters (Alternautas, 2016)
The analysis of encounters of alterity, within the context of seduction and in a touristic environment, gives us the possibility to reflect upon powerful relations between gender, race and class. How can femininities and masculinities be analysed in an intercultural context and asymmetrical socio-economic situations? The focus on seduction strategies gives the possibility to investigate gender staging in this specific context of cultural-mixing. The commercial exploitation of romance interrogates the lack of transcendence in post-modern societies. The encounter of fantasies allows us to study the complex identity process marked by domination logics.